The Belt and Road Initiative and Chinese Influence in Latin America (قضايا سياسية, 2024)
The Belt and Road Initiative, which was announced by Chinese President Xi Jinping in 2013, represents an economic strategy through which China seeks to strengthen its communication with the different countries of the world and secure its access to all international markets in addition to the political dimensions of  the initiative, which enable China to strengthen its position as one of the major powers. To enhance that vision and achieve its goals, China sent an invitation to Latin American countries in 2018 to join the initiative, and they did with the aim to achieve their economic goals, the most important of which are strengthening infrastructure and achieving development requirements. On the other hand, China sought to create influence in the Latin American region and enhance its international standing through the initiative.